Longitudinal Dimensions of Polygon-shaped Planetary Waves - Ibragimov, Ranis N.; Lin, Guang (Journal of Applied Nonlinear Dynamics, 2026)
Polygon-shaped longitudinal large-scale waves are described by means of higher-order shallow water approximation corresponding to the Cauchy–Poisson free boundary problem on the stationary motion of a perfect incompressible fluid circulating around a circle. It is shown that there are four basic physical parameters, which exert an influence on a wave number (or wave length), which is one of the basic values used to characterize the planetary flow pattern in mid-troposphere. Some analogy with the jet-stream following hexagon-shaped path at Saturn’s north pole is observed.